An investigation of inconsistent projections and artefacts in multi-pinhole SPECT with axially aligned pinholes - Kench, Peter; Lin, Jianyu; Gregoire, M; Meikle, Steven (Institute of Physics Publishing, 2011)
Multiple pinholes are advantageous for maximizing the use of the available field of view (FOV) of compact small animal single photon emission computed tomography (SPECT) detectors. However, when the pinholes are aligned axially to optimize imaging of extended objects, such as rodents, multiplexing of the pinhole projections can give rise to inconsistent data which leads to 'ghost point' artefacts in the reconstructed volume. A novel four pinhole collimator with a baffle was designed and implemented to eliminate these inconsistent projections. Simulation and physical phantom studies were performed to investigate artefacts from axially aligned pinholes and the efficacy of the baffle in removing inconsistent data and, thus, reducing reconstruction artefacts. SPECT was performed using a Defrise phantom to investigate the impact of collimator design on FOV utilization and axial blurring effects. Multiple pinhole SPECT acquired with a baffle had fewer artefacts and improved quantitative accuracy when compared to SPECT acquired without a baffle. The use of four pinholes positioned in a square maximized the available FOV, increased acquisition sensitivity and reduced axial blurring effects. These findings support the use of a baffle to eliminate inconsistent projection data arising from axially aligned pinholes and improve small animal SPECT reconstructions.